Bamboo-like N-doped carbon tubes encapsulated CoNi nanospheres towards efficient and anticorrosive microwave absorbents - Liang, Lei-Lei; Liu, Zhuo; Xie, Li-Jing; Chen, Jing-Peng; Jia, Hui; Kong, Qing-Qiang; Sun, Guo-Hua; Chen, Cheng-Meng (Carbon (New York), 2021)
The exploration of high-efficient, environment-stable, and cost-effective microwave absorption (MA) materials is of great significance for commercial application, and the main challenge lies in how to integrate these fascinating features using facile strategies. Herein, a one-step synergistic catalytic pyrolysis strategy was developed to construct bamboo-like N-doped carbon tube encapsulated cobalt-nickel alloy. As for a bamboo-like N-doped carbon tube, it not only provides abundant cavities for the generation of the induced current, but also induces uneven distribution of local charges from the N-doping, which results in the enhanced conduction loss and polarization relaxation. More importantly, the confinement of CoNi alloy into carbon tube effectively prevents the agglomeration of magnetic CoNi nanoparticles and simultaneously protects the CoNi alloy from corrosion, which is favorable for preserving its original magnetic properties and achieving stable MA performance in extreme chemical environment. On the basis of the combined effect, the optimized CoNi–N/C-700 achieves strong absorption of −55.62 dB and broad bandwidth of 4.25 GHz with an ultrathin thickness of 1.45 mm and low filler loading of 10 wt%, outperforming most bimetal-based microwave absorbers. This one-step synthetic strategy may pave a new way to design and construct high-efficient and anti-corrosion microwave absorbers for future large-scale applications. A one-step synergistic catalytic pyrolysis strategy was proposed to prepare the bamboo-like N-doped carbon tubes encapsulated CoNi alloy with exceptional microwave absorption performance and good corrosion resistance characteristic. [Display omitted] •A one-step synergistic catalytic pyrolysis was proposed to fabricate bamboo-like carbon tubes encapsulated CoNi nanospheres.•Pyrolysis temperature effects graphitization degree, nitrogen amounts, and magnetic properties.•The unique structure shows superior microwave absorption at an ultrathin thickness and a low filler loading.•Conductivity loss, polarization loss, and magnetic response give excellent absorption characteristics.•The outer carbon shell prevents corrosion of the CoNi alloy.